PERSEPSI PENGUNJUNG OBJEK WISATA KOLAM RENANG IDAMAN DI KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Syadzwina Syadzwina; Emmy Sri Mahreda; Emmy Lili Mantik; Eko Rini Indrayatie (EnviroScienteae, 2021)
Attractions selected community based on the wishes and the needs of the individual. Society simply adjust to what is offered by tourist attractions. The presence of competition of several swimming pools means that each manager needs to consider the development strategy so that Visitor will never leave their swimming pool. It is important to know what visitors want for a tourist attraction prior to carrying out development. Visitor perception is necessary, it is the first step in the strategy of tourism development. The purpose of this research was to analyze the Visitor perceptions of the Idaman swimming pool tourist attraction. This research is descriptive quantitative. The method used is the Likert scale using 5 scales. Visitors' perception of the existence of a tourist attraction for swimming pools is generally positive. Visitors' perception strongly agree (SS) in terms of environmental hygiene, environmental safety, water quality is good, accessibility accessible, convenient parking, ticket rates are very affordable compared with the acquired facilities, hospitality officer to serve visitors during this and the existence of a tourist attraction that is beneficial to the local society.